Case Reports in Perinatal Medicine : Official Journal of the World Association of Perinatal Medicine (De Gruyter, 2012)
Continuous readers' interest and significant relevance of case reports inspired the Editors and Publishers of the Journal of Perinatal Medicine (JPM) to found the journal Case Reports in Perinatal Medicine. (CRPM) The aims & scope of CRPM are very similar to those of JPM: both journals publish interdisciplinary, innovative, evidenced-based and basic science research that is informative and useful for daily clinical practice.